Peningkatan Production Flexibility pada Etios di PT Toyota Motor Manufacturing Indonesia - Sugiono, Andrieas; Palit, Herry Christian (Jurnal Titra, 2014)
Currently, the system of car order at PT Toyota Motor Manufacturing Indonesia (PT TMMIN) is not flexible. The orders must be fixed 2 months before their production month (firm order). PT TMMIN gives customer a privilege for changing their grade after firm order or Weekly Order Change (WOC). In this paper, WOC is applied for product Etios. The application of WOC is done in Global Production Planning System (GPPS) by changing the system. It is used to make the orders more flexible after firm order. This application impacts on unique import part as well and requires 10 percent additional safety stock allocation. Additional safety stock needs additional inventory cost as much as Rp 6XX million rupiahs.